2014
DOI: 10.1007/s10980-014-0107-y
|View full text |Cite
|
Sign up to set email alerts
|

What can studies of woodland fragmentation and creation tell us about ecological networks? A literature review and synthesis

Abstract: The development of ecological networks could help reverse the effects of habitat fragmentation on woodland biodiversity in temperate agricultural landscapes. However, efforts to create networks need to be underpinned by clear evidence of the relative efficacy of local (e.g. improving or expanding existing habitat patches) versus landscape-scale actions (e.g. creating new habitat or corridors in the landscape matrix). Using cluster analyses we synthesised the findings of 104 studies, published between 1990 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 133 publications
(111 reference statements)
1
65
0
Order By: Relevance
“…Reserve size does not always reflect population size nor species diversity, which is an argument in favour of increasing the number of small reserves, especially where key habitat features and rare species or structures occur [18,153], as is the case in the projected conservation zones ( Figure 5). As recently reviewed by Humphrey et al [154], forest patch characteristics (stand structure, species composition and habitat heterogeneity) are of overriding importance for the conservation of all species groups. In that perspective, land zoning should not be restricted to large forest territories, where the possibility to create a reserve network at the landscape and regional scale is far less complicated than in a mosaic of small private landowners with different perceptions of forest and agricultural land management.…”
Section: Management Considerations and Limitations Of Applying Forestmentioning
confidence: 99%
See 1 more Smart Citation
“…Reserve size does not always reflect population size nor species diversity, which is an argument in favour of increasing the number of small reserves, especially where key habitat features and rare species or structures occur [18,153], as is the case in the projected conservation zones ( Figure 5). As recently reviewed by Humphrey et al [154], forest patch characteristics (stand structure, species composition and habitat heterogeneity) are of overriding importance for the conservation of all species groups. In that perspective, land zoning should not be restricted to large forest territories, where the possibility to create a reserve network at the landscape and regional scale is far less complicated than in a mosaic of small private landowners with different perceptions of forest and agricultural land management.…”
Section: Management Considerations and Limitations Of Applying Forestmentioning
confidence: 99%
“…Such cooperative cross-boundary projects are unavoidable for efficient conservation [144], as ecological networks development in temperate agricultural areas needs to focus on enhancing the size of existing habitat patches and reducing isolation between patches [154].…”
Section: Management Considerations and Limitations Of Applying Forestmentioning
confidence: 99%
“…Indeed, several studies have found patch characteristics to be more important than patch area (Benton et al 2003, Heikkinen et al 2004, Wretenberg et al 2010, Galitsky and Lawler 2015, Humphrey et al 2015. Even where the landscape structure was similar, there could be differences in the quality of habitat (the amount and diversity of structures and processes characteristic of each habitat) for birds within patches that were ostensibly the same.…”
Section: Structural Elements Gradient Lengths Spatial Scales and Smentioning
confidence: 99%
“…Aars and Ims, 1999;Fischer and Lindenmayer, 2002;Haddad et al, 2003;Haddad and Tewksbury, 2005;Robertson and Radford, 2009), but their effectiveness is variable and species-specific (Baum et al, 2004;Humphrey et al, 2014;Prevedello and Vieira, 2010). In addition, it is important to distinguish between foraging behaviour and dispersal behaviour, and between individual movements and population level benefits (which is not necessarily an implied result -Gilbert- Norton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%